Synthesis, Characterization and Antimicrobial Activity of Some Novel 1-substituted Benzimidazole Derivatives - Isik, Erkut; Astley, Demet; Yuksekdanaci, Seda; Yasa, Ihsan (Letters in Drug Design & Discovery, 2020)
Background: Benzimidazole derivatives are an important class of heterocyclic compounds in organic chemistry as they are related to a wide range of biological properties, including antimicrobial activity. Methods: A series of 1-naphthoyl and benzoyl benzimidazole derivatives were synthesised, identified and screened for their antimicrobial activities against a number of different test organisms such as Escherichia coli, Pseudomonas aureginosa, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis, Bacillus cereus, Salmonella typhimurium, Candida albicans (yeast). Results and Discussion: Benzimidazole derivatives (3a-d) were synthesised by using 4 different aminoacids. L-methionine, L-isoleucine, D-Phenylysine and L-Phenylamine as starting materials in the study. Experimental studies involve the use of benzimidazole derivatives (3a-d) of the selected amino acids to synthesize the benzoyl and naphthoyl derivatives of benzimidazole (4a-d, 5a-c). The structures of the synthesized compounds were confirmed by spectroscopic analyses (FTIR, 1HNMR, 13C-NMR) and elemental analysis. Conclusion: In this study, only one compound (5a) showed a low MIC value against the eukaryotic microorganism C. albicans. The other six compounds showed higher antimicrobial activities against the prokaryotes C. albicans which is a normal flora in the mouth but is one of the organisms that cause infections leading to the weakening of the human immune system. Compound 5a is a candidate for future alternative antimicrobial drugs against C. albicans infections. In addition, compound 5a has a potential to be used as an inhibitor against P. aureginosa for the treatment of cystic fibrosis.
Keywords: Synthesis